Social cognition in individuals with schizophrenia, autism spectrum disorder and controls - Juliana Gioia Negrão; Ana Alexandra Caldas Osório; Rodrigo Bressan; Ary Gadelha; Vivian Renne Gerber Lederman; Tally Lichtenstein Tafla; Ana Olívia Fonseca; Tatiana Pontrelli Mecca; Arthur Berberian; Mariana Lederman Edelstein; José Salomão Schwartzman (Jornal Brasileiro de Psiquiatria, 2023)
ABSTRACT Objective: The aim of this study was to compare the social cognition profiles of male adults with ASD (n = 15), SCHZ (n = 16) and controls (n = 20). Change the second sentence of the abstract. Methods: A cross-sectional assessment of social cognition domains with emotional face perception with eye tracking was performed, and two IQ measures (Verbal IQ and Performance IQ) (Wechsler Adult Intelligence Scale), and the DSM-IV Structured Clinical Interview were applied. Results: There were no significant differences in terms of average performance in social cognition tests or eye tracking tasks between the ASD and SCHZ groups. However, both had lower performances in most cases when compared to the control group. In the social cognition tasks, individuals in the control group performed better than both clinical groups. Conclusion: Although differences were identified between individuals with ASD and SCHZ, it was not possible to determine patterns or to differentiate the clinical groups.